Số liệu thống kê công nghiệp Việt Nam ( 1976 - 1991 ) - Sự phân bố, cơ cấu, qui mô và hiệu quả (Tổng cục Thống kê, 1992)
Sự phân bố, cơ cấu, qui mô và hiệu quả của Số liệu thống kê công nghiệp Việt Nam ( 1976 - 1991 )